Internal filament modulation in low-dielectric gap design for built-in selector-less resistive switching memory application. (16th January 2018) - Chen, Ying-Chen; Lin, Chih-Yang; Huang, Hui-Chun; Kim, Sungjun; Fowler, Burt; Chang, Yao-Feng; Wu, Xiaohan; Xu, Gaobo; Chang, Ting-Chang; Lee, Jack C
Abstract: Sneak path current is a severe hindrance for the application of high-density resistive random-access memory (RRAM) array designs. In this work, we demonstrate nonlinear (NL) resistive switching characteristics of a HfO x /SiO x -based stacking structure as a realization for selector-less RRAM devices. The NL characteristic was obtained and designed by optimizing the internal filament location with a low effective dielectric constant in the HfO x /SiO x structure. The stacking HfO x /SiO x -based RRAM device as the one-resistor-only memory cell is applicable without needing an additional selector device to solve the sneak path issue with a switching voltage of ~1 V, which is desirable for low-power operating in built-in nonlinearity crossbar array configurations.